Effectiveness of Dextrose Prolotherapy for Rotator Cuff Tendinopathy: A Systematic Review. Issue 3 (4th December 2019) - Catapano, Michael; Zhang, Kailia; Mittal, Nimish; Sangha, Harpreet; Onishi, Kentaro; de SA, Darren
Abstract : Objective: To systematically review and evaluate the efficacy and complication profile of prolotherapy using hyperosmolar dextrose solution injection for rotator cuff tendinopathy. Literature Survey: MEDLINE, EMBASE, CINAHL, and the Cochrane Central Register of Controlled Trials (from inception to 1 July, 2019). Methodology: A comprehensive search was completed to identify randomized controlled trials addressing prolotherapy using hyperosmolar dextrose solution for rotator cuff tendinopathy. Two reviewers independently screened the titles, abstracts, and full texts, and then extracted data from eligible studies. All reported outcome measures and complications were analyzed descriptively. Synthesis: Five studies satisfied inclusion criteria. Included studies analyzed a total of 272 participants with a final follow‐up ranging from 6 weeks to 12 months. Prolotherapy differed greatly among studies. Two studies used a multisite enthesis injection protocol while the other three used ultrasound‐guided protocols. Two of the studies used an intrasubstance supraspinatus injection and three used a supraspinatus enthesis injection. Control groups consisted of nonoperative rehabilitation including physical therapy and medical management in three studies, supraspinatus saline enthesis injection in one study, and corticosteroid injection in one study. There was statistically significant improvement in pain intensity with multisite injection protocols compared to physical therapy and medical management in both studies. Ultrasound‐guided supraspinatus injection trials did not find any statistically significant difference in pain intensity, range of motion, strength, function, or ultrasound characteristics compared to controls of enthesis saline injection or corticosteroid. The complication rate was low, with only 6/272 participants experiencing adverse events consisting of transient increase in pain for 1 to 2 days postintervention. Conclusions: Prolotherapy with hyperosmolar dextrose solution is a potentially effective adjuvant intervention to physical therapy for patients with rotator cuff tendinopathy ranging from tendinosis to partial‐thickness and small full‐thickness tears. Further studies are necessary to determine effects in subpopulations as well as optimal technique including dextrose concentration, volume, and location.